Estimating farm‐level private expenditure on veterinary medical inputs in England. (15th March 2014) - Gilbert, W.; Rushton, J.
Abstract : The current re‐evaluation of responsibility and cost sharing between the public and private sectors with reference to animal health and welfare (AHW) would be improved by a greater understanding of the contributions made at farm level. This knowledge would facilitate the design of a cost‐sharing system which best balances technical, economic and political objectives. This paper presents a framework by which the farm‐level investment in AHW can be assessed. An evaluation of data available for the framework was made and, as a benchmark, an estimate of total expenditure on veterinary medical inputs for commercial agricultural holdings in England calculated. In 2010/2011 it is calculated that farmers on commercial holdings in England spent £230 million on veterinary medicines and fees, with an additional £160 million being spent for horses kept on non‐commercial holdings. By contrast, for 2012/2013, Defra budgeted £277 million on AHW. The results presented emphasise the critical importance of generating sufficient evidence to support the development of an efficient, equitable and sustainable AHW strategy.